Analisis Miskonsepsi IPA Materi Fotosintesis Ditinjau dari Perspektif Siswa - Zulfa, Farah Naila; Ngazizah, Nur; Pangestika, Rintis Rizkia (Jayapangus Press, 2025)
The research was conducted to analyze the existence of science misconceptions in photosynthesis material through students' perspectives. Misconceptions in students are misunderstandings of concepts understood by students that can affect student understanding in learning. Photosynthesis material is complex material so that misconceptions often occur in students. The research was conducted on 20 grade VI elementary school students using a three tier diagnostic test to measure students' understanding of the material concept. This research is a qualitative research with a descriptive approach. Data collection techniques were carried out with tests, interviews, observations, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions. The results of the study based on the analysis of the three tier diagnostic test showed that 17.14% of students were in the category of understanding the concept, 44.29% of students experienced misconceptions with positive misconceptions of 7.14%, negative misconceptions of 12.86%, and pure misconceptions of 24.29%, other categories were guessing as many as 12.86% of students, and did not understand the concept as many as 25.71%. These results show that there are students who have identified misconceptions in photosynthesis material with moderate categories. The highest misconception occurred in the material coverage of the time of photosynthesis which was 90% with a high category and the lowest misconception occurred in the material coverage of the purpose of photosynthesis which was 10% with a low category. The results of data analysis based on student perspectives, misconceptions occur due to student preconceptions, teacher explanations, and other teaching materials. The conclusion based on the data obtained is that grade VI elementary school students experience misconceptions of photosynthesis science material.